2014
DOI: 10.1371/journal.pone.0105347
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Development of Asthma and Allergic Diseases in Relation to International Immigration: The Leading Role of the Environment Confirmed

Abstract: BackgroundThe prevalence of asthma and allergic diseases is rising worldwide. Evidence on potential causal pathways of asthma and allergies is growing, but findings have been contradictory, particularly on the interplay between allergic diseases and understudied social determinants of health like migration status. This review aimed at providing evidence for the association between migration status and asthma and allergies, and to explore the mechanisms between migration status and the development of asthma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 46 publications
5
67
1
2
Order By: Relevance
“…9 Previous studies have found that the risk of developing allergic diseases increases in those immigrating from low-income countries to Western countries, 9 and the prevalence increases with longer residence in the host country. 10 These results support the "healthy immigrant effect" found in various fields of health research, where recent immigrants tend to be healthier than the native population, but the differences vanish over time with exposures in the host country or the adoption of adverse health behaviours. The mechanism behind differences in allergic conditions by immigration status is still unclear, but the "biodiversity hypothesis" provides a possible explanation.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…9 Previous studies have found that the risk of developing allergic diseases increases in those immigrating from low-income countries to Western countries, 9 and the prevalence increases with longer residence in the host country. 10 These results support the "healthy immigrant effect" found in various fields of health research, where recent immigrants tend to be healthier than the native population, but the differences vanish over time with exposures in the host country or the adoption of adverse health behaviours. The mechanism behind differences in allergic conditions by immigration status is still unclear, but the "biodiversity hypothesis" provides a possible explanation.…”
supporting
confidence: 78%
“…25 Second-generation immigrants have been found consistently to have higher rates of allergies than first-generation immigrants. 10 Third, some studies had very small sample sizes, resulting in imprecise estimates from which it was difficult to draw conclusions. 23,25 In general, results from this study are consistent with previous studies with similar study design, that is, studies using self-reported allergies as the outcome, looking at first-generation immigrants only and having a relatively large sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not explain why the prevalence of asthma is generally lower in low-income countries, where especially residents in urban areas in tropical climates may be more exposed to indoor and outdoor pollution than in higher income countries. Research on migrants has shown that the prevalence of asthma in people migrating to high-income countries rises over time, with increased length of exposure to determinants of health in the host country [62]. More research is needed to determine which environmental factors in westernised societies drive this change in susceptibility to asthma.…”
Section: Implications For Research and Policymentioning
confidence: 99%
“…Within Western countries however, further differences in prevalence between native born populations and non-Western migrants, with migrants generallyon average haveing lower prevalence rates thanrelative to native born populations in Western countries [2]. HEvidence does suggest however, that the prevalence of wheeze and asthma symptoms may be higher in migrants compared to their peers in their countries of origin, and prevalence and severity the risk of development and symptoms increase in increaseseverity with each additional year of residence in high-prevalence countires [2][3][4].…”
Section: Emily S Petherick Neil Pearce Jordi Sunyer John Wright Otmentioning
confidence: 99%